Concreting works for structure (slab, column, beam) for proposed 14 units double storey semi-detached houses and 236 units double storey terrace houses on parent Lot 4044, Block 18, Salak Land District, at Jalan Bako (Sourabaya), Kuching Sarawak / Lukhman Arip - Arip, Lukhman (Universiti Teknologi Mara, Perak, 2014)
This report is based on my experienced practical training that conducted within five (5) months. Also, lecturer had given out the task that based on scope of work in the company and I chose Concreting work as my final topic. I hope this topic can explain in detail what I have earn during this practical training and can be easily be read and understand.